Perbandingan Zakat Produktif dan Zakat Konsumtif dalam Meningkatkan Kesejahteraan Mustahik - Khalifah Muhamad Ali; Nydia Novira Amalia; Salahuddin El Ayyubi (AL-MUZARA'AH, 2016)
This study aims to compare the effectiveness of productive and consumptive zakat distribution in poverty alleviation. This study uses a CIBEST (Center of Islamic Business and Economics Studies) model which measures not only the material aspect of the poverty, but also the spiritual aspect of the respondents. The results proves that both zakat distribution types can increase welfare as well as reduce poverty of mustahik. Productive zakat can alleviate poverty more than consumtive zakat.